School violence in context : culture, neighborhood, family, school, and gender - Benbenishty, Rami.; As{u4BF2}, Ron. (New York : Oxford University Press, 2005)
'Draws on surveys comparing Jewish and Arab-Israeli students with students in the United States. Presents an empirically-based model for understanding school violence, highlighting both universal and culturally specific patterns of school violence'--Provided by publisher.
Includes bibliographical references (p. [197]-210).
Keywords: School violence -- Social aspects -- Israel -- Case studies; School violence -- Social aspects -- United States -- Case studies; School violence -- Cross-cultural studies